2011
DOI: 10.4067/s0717-95022011000400042
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Study of the Proximal Femur in Malay Population

Abstract: SUMMARY:Clinical practice in our country showed a lack of suitable implants that perfectly match the anthropometry of the local population. However, there have been no reports or comprehensive studies conducted to substantiate this argument. We therefore prospectively studied 120 hips from sixty subjects with an average age of 25±5.18 years old. The average weight and height were 61.48±13.84 kg and 1.65±9.63 m respectively. The exclusion criteria were pregnant woman, those who had injury to the hip joint, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
(17 reference statements)
4
23
2
Order By: Relevance
“…Approximately 200,000 of them are those who reside in the UK and the USA. This is a case which negatively affects in the short-term and the long-term success of operations carried out in Asian and African countries owing to morphological incongruity of implant bones, where the proximal femoral morphometry is different from the one in Western countries, except for the Japanese who produce in accordance with their people's proximal femoral morphometry thanks to their highly-developed prosthesis industry (Baharuddin et al, 2011;Murlimanju et al, 2012;Atilla et al, 2007;Hoaglund and Low, 1980; *Correspondence to: Mustafa G€ uvençer, Department of Anatomy, Faculty of Medicine, University of Dokuz Eyl€ ul, Balçova, 35340-Izmir, Turkey. E-mail: mustafa.guvencer@deu.edu.tr Isaac et al, 1997;Rubin et al, 1992;Mahaisavariya et al, 2002;Noble et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 200,000 of them are those who reside in the UK and the USA. This is a case which negatively affects in the short-term and the long-term success of operations carried out in Asian and African countries owing to morphological incongruity of implant bones, where the proximal femoral morphometry is different from the one in Western countries, except for the Japanese who produce in accordance with their people's proximal femoral morphometry thanks to their highly-developed prosthesis industry (Baharuddin et al, 2011;Murlimanju et al, 2012;Atilla et al, 2007;Hoaglund and Low, 1980; *Correspondence to: Mustafa G€ uvençer, Department of Anatomy, Faculty of Medicine, University of Dokuz Eyl€ ul, Balçova, 35340-Izmir, Turkey. E-mail: mustafa.guvencer@deu.edu.tr Isaac et al, 1997;Rubin et al, 1992;Mahaisavariya et al, 2002;Noble et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that Indonesian population has smaller femoral head dimension compared with Western population (Noble et al, 1988;Rubin et al, 1989;Hussmann et al, 1997). However, among southeast Asian, such as Thai and Malaysian, our study showed that Indonesia has larger femoral head morphometry (Baharuddin et al;Mahaisavariya et al, 2002). Extramedullary dimensions (femoral head position, femoral head offset, and ante version angle) play an important role in maintaining proper hip kinematics and it will affect the satisfaction of post-operative result (Sugano et al, 1999;Ranawat & Rodriguez, 1997).…”
Section: Discussionmentioning
confidence: 61%
“…Differences in genetics, lifestyle, applied force and their distribution affect the build and stature size between ethnicity as shown in several studies (Hoaglund & Low, 1980;Igbigbi & Msamati, 2002;Baharuddin et al, 2011). Based on some studies, it showed that the eastern population has relatively smaller measurement compared with Western population.…”
Section: Introductionmentioning
confidence: 98%
“…We prospectively acquired the computed tomography (CT) images from 60 healthy hips prior to designing the cementless femoral stem in accordance with the peculiar morphology of the Asian population (13)(14)(15)(16). The design process used a three-dimensional femora model that provides more anthropometric information and accurate measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The cementless femoral stem was designed to optimally fit and fill the endosteal canal as shown in Fig. The 3D femora model chosen for finite element study was the "average" femora from the previous study (13)(14)(15)(16). Interquartile range descriptive analysis was used as the stem design profile, and nonlinear finite element analysis was conducted to predict the outcome of the early stage after the surgery according to the standard protocol of virtual implantation (2)(3)(4).…”
Section: Methodsmentioning
confidence: 99%